Conversion of Mevalonic Acid to γ,γ-Dimethylallyl Pyrophosphate by Mycoplasma - Henrikson, Carl V. (1966)
Henrikson, Carl V. (University of South Dakota, Vermillion), and Paul F. Smith. Conversion of mevalonic acid to γ,γ-dimethylallyl pyrophosphate by Mycoplasma. J. Bacteriol. 92:701–706. 1966.—Three representative strains of Mycoplasma, M. laidlawii strain B, Mycoplasma sp. avian strain J, and M. hominis type 2 strain O7, were examined for the presence or absence of enzymes associated with the biosynthetic pathway from mevalonic acid to γ,γ-dimethylallyl pyrophosphate. M. laidlawii served as a control organism, since it is capable of de novo biosynthesis of carotenoids. All four enzymes, namely, adenosine triphosphate (ATP)-mevalonate 5-phosphotransferase (EC 2.7.1.36), ATP-5-phosphomevalonate phosphotransferase (EC 2.7.4.2), ATP-5-pyrophosphomevalonate carboxy-lyase (EC 4.1.1.33), and isopentenylpyrophosphate Δ(3),Δ(2)-isomerase (EC 5.3.3.2), were demonstrated in this organism. Mycoplasma sp. avian strain J, which contains all enzymes necessary for the biosynthesis of mevalonic acid, lacks the first three of the above enzymes but contains isopentenyl pyrophosphate Δ(3),Δ(2)-isomerase. M. hominis, which lacks the enzymes necessary for the biosynthesis of mevalonic acid, also is deficient in the enzymes involved in its conversion to γ,γ-dimethylallyl pyrophosphate.